Pengaruh Brand Trust, Influencer Marketing, dan Lifestyle Terhadap Keputusan Pembelian Produk Eiger Pada Generasi Z - Hidaya Turrohmah; Titik Desi Harsoyo (Journal of Indonesian Economic Research, 2026)
This study aims to analyze the influence of Brand Trust, Influencer Marketing, and Lifestyle on Eiger product purchasing decisions among Generation Z. The sample in this study was 100 Generation Z respondents who had purchased Eiger products. The sampling technique used non-probability sampling with purposive sampling through an online questionnaire. The results of the instrument test indicate that all questions used in this study are valid and reliable. The results of the classical assumption test indicate that the data in this study are normally distributed and free from multicollinearity and heteroscedasticity. The data analysis technique employed in this study is multiple linear regression analysis. Based on the results of the study, it can be proven that (1) Brand Trust has a positive and significant effect on Eiger product purchasing decisions among Generation Z. (2) Influencer Marketing has a positive and significant effect on Eiger product purchasing decisions among Generation Z. (3) Lifestyle has a positive and significant effect on Eiger product purchasing decisions among Generation Z. Brand Trust is the variable with the most dominant influence. The coefficien of determination test yields an Adjusted R Square value of 0.865, demonstrating that the three independent variabel account for 86.5% of the variance in purchase decisions.